Postural sway in diabetic peripheral neuropathy among Indian elderly - Dixit, Snehil (Indian J Med Res, 2015)
BACKGROUND & OBJECTIVES: Diabetic peripheral neuropathy (DPN) is a major complication of type 2 diabetes and have long term complications on the postural control of the affected population. The objectives of this study were to evaluate postural stability in patients with DPN and to examine correlation of Michigan Neuropathy Screening Instrument (MNSI) with duration of diabetes, age and postural stability measures. METHODS: Participants were included if they had clinical neuropathy which was defined by MNSI. Sixty one patients gave their consent to participate in the study and were evaluated on posturography for postural stability measures in four conditions. Repeated measures of analysis of variance (RANOVA) was used to analyze the changes in postural stability measures in different conditions. RESULTS: An increase in mean value of postural stability measures was observed for velocity moment 20.4±1.3, 24.3±2.2, 42.3±20.7, 59±43.03, mediolateral displacement 0.21±0.10, 0.22±0.18, 0.03±0.11, 0.34±0.18, and anteroposterior displacement 0.39 ± 0.09, 0.45±0.12, 0.47±0.13, 0.51±0.20 from EO to EC, EOF, and ECF, respectively. There was a significant difference (P<0.05) in participants with DPN, with greater sway amplitude on firm and foam surface in all the conditions. Moderate correlation of MNSI with age (r=0.43) and postural stability measures were also observed. INTERPRETATION & CONCLUSIONS: Evaluation of postural stability in Indian DPN population suggests balance impairments on either firm and foam surfaces, with greater likelihood of fall being on foam or deformable surfaces among elderly adults with neuropathy (CTRI/2011/07/001884).